The Effect of Anatomical Location of Lymph Node Metastases on Cancer Specific Survival in Patients with Clear Cell Renal Cell Carcinoma - Nini, Alessandro; Larcher, Alessandro; Cianflone, Francesco; Trevisani, Francesco; Terrone, Carlo; Volpe, Alessandro; Regis, Federica; Briganti, Alberto; Salonia, Andrea; Montorsi, Francesco; Bertini, Roberto; Capitanio, Umberto (Frontiers in Surgery, 2018)
Background: Positive nodal status (pN1) is an independent predictor of survival in renal cell carcinoma (RCC) patients. However, no study to date has tested whether the location of lymph node (LN) metastases does affect oncologic outcomes in a population submitted to radical nephrectomy (RN) and extended lymph node dissection (eLND). Objective: To describe nodal disease dissemination in clear cell RCC (ccRCC) patients and to assess the effect of the anatomical sites and the number of nodal areas affected on cancer specific mortality (CSM). Design, setting and partecipants: The study included 415 patients who underwent RN and eLND, defined as the removal of hilar, side-specific (pre/paraaortic or pre/paracaval) and interaortocaval LNs for ccRCC, at two institutions. Outcome measurement and statistical analysis: Descriptive statistics were used to depict nodal dissemination in pN1 patients, stratified according to nodal site and number of involved areas. Multivariable Cox regression analyses and Kaplan-Meier curves were used to explore the relationship between pN1 disease features and survival outcomes. Results and limitations: Median number of removed LN was 14 (IQR 9-19); 23% of patients were pN1. Among patients with one involved nodal site, 54% and 26% of patients were positive only in side-specific and interaortocaval station, respectively. The most frequent nodal site was the interaortocaval and side-specific one, for right and left ccRCC, respectively. Interaortocaval nodal positivity (HR 2.5, CI95%: 1.3-3.9, p<0.01) represented an independent predictor of CSM. Conclusions: When ccRCC patient harbour nodal disease, its spreading can occur at any nodal station without involving the others. The presence of interoartocaval positive nodes does affect oncologic outcomes. Patient summary: Lymph node invasion in patients with clear cell renal cell carcinoma is not following a fixed anatomical pattern. An extended lymph node dissection, during treatment for primary kidney tumour, would aid patient risk stratification and multimodality upfront treatment.